The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

OHADA and the Making of Transnational Commercial Law in Africa - Bashi Rudahindwa, Jonathan (Law and Development Review, 2018)
The Organisation for Harmonisation of Business Law in Africa (OHADA) was established in October 1993 with the ambitious aim of inciting economic development in its Member States. Through the adoption of Uniform Commercial Laws, the organisation is expected to create an enabling environment for business development, thereby providing for a path to economic growth and subsequent development. In light of this professed aim, both the transnational methodological approach and comparative law theories are used in this paper to critically analyse the various processes conducted under the OHADA banner and to engage in discussions on the highly debated role of law as a vehicle for development in sub-Saharan Africa. This exercise, which proves crucial in order to trace its origin within the global governance and law and development theories, allows us to present OHADA as a transnational legal system, while also highlighting both its strengths and limitations.
Keywords: Law and development; Law reform; Legislative unification; OHADA; Transnational law

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules